A Novel Zinc-Based MOF Featuring 2,4,6-Tris-(4-carboxyphenoxy)-1,3,5-triazine: Structure, Adsorption, and Photocatalytic Activity - Magdalena Angelova; Hristina Lazarova; Vanya Kurteva; Rositsa Nikolova; Rusi Rusew; Boris Shivachev (Crystals)
A metal–organic framework, MOF-S1, was synthesized via a solvothermal reaction between 2,4,6-tris-(4-carboxyphenoxy)-1,3,5-triazine (TCPT) and zinc nitrate hexahydrate. Single-crystal and powder X-ray diffraction analyses confirmed the formation of hexagonal rod-shaped crystals with a trigonal (P-31c) structure featuring a two-fold interpenetrated 3D framework. A comprehensive characterization—including NMR spectroscopy, thermogravimetric analysis, and surface area measurements (using Langmuir, t-plot, Horváth–Kawazoe, and Dubinin–Radushkevich models)—revealed an ultramicroporous material with a Langmuir surface area of 711 m2/g and a median pore width of ~6.5 Å. Adsorption studies using Congo Red, Methylene Blue, Methyl Orange, and Rhodamine B demonstrated the rapid uptake and effective removal from aqueous solutions, with kinetic modeling indicating a dominant chemisorption mechanism. Photocatalytic tests under UV irradiation yielded degradation efficiencies of ~93% for Methyl Orange and ~74% for Rhodamine B. These findings suggest that MOF-S1 is a promising candidate for wastewater treatment applications and UV-related processes, offering a strong adsorption capacity and thermal stability.